2016
DOI: 10.1155/2016/2386728
|View full text |Cite
|
Sign up to set email alerts
|

Family Dynamics and Personal Strengths among Dementia Caregivers in Argentina

Abstract: This study examined whether healthier family dynamics were associated with higher personal strengths of resilience, sense of coherence, and optimism among dementia caregivers in Argentina. Caregivers are usually required to assist individuals with dementia, and family members have typically fulfilled that role. Personal strengths such as resilience, sense of coherence, and optimism have been shown to protect caregivers from some of the negative experiences of providing care, though the family-related variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 65 publications
6
20
0
1
Order By: Relevance
“…As described by Gitlin et al, 68 most of the caregivers found in caregiving a chance to "return the favour" to their relatives and the opportunity to do activities together, reducing both caregiver burden and behavioural symptoms of dementia, which is in agreement with our findings. Findings from Elnasseh et al 69 are consistent with past literature showing that the quality of previous familiar relationship is relevant when a family member becomes a caregiver. In families with healthier dynamics, caregivers are more likely to have greater personal strengths, while families with poor affinity are more likely to experience increased caregiver burden.…”
Section: Discussionsupporting
confidence: 81%
“…As described by Gitlin et al, 68 most of the caregivers found in caregiving a chance to "return the favour" to their relatives and the opportunity to do activities together, reducing both caregiver burden and behavioural symptoms of dementia, which is in agreement with our findings. Findings from Elnasseh et al 69 are consistent with past literature showing that the quality of previous familiar relationship is relevant when a family member becomes a caregiver. In families with healthier dynamics, caregivers are more likely to have greater personal strengths, while families with poor affinity are more likely to experience increased caregiver burden.…”
Section: Discussionsupporting
confidence: 81%
“…They show that burden is usually associated with lower socio-economic status and with poor outcomes for the dependent older person (Chen et al, 2016). Some studies identify associations between positive family dynamics and family cohesion (defined in general terms) and reduced carer burden (Elnasseh et al, 2016;Perrin et al, 2013). These findings are closely in line with those of similar studies in high income countries.…”
Section: Introductionsupporting
confidence: 69%
“…The most relevant study we found reported an association between personal strengths and enhanced psychosocial functioning. The strengths identified included resilience, optimism, and a sense of coherence (Elnasseh et al 2016). Resilience was defined as effective coping in times of adversity, optimism as being positive, and sense of coherence as being efficient by using positive coping methods.…”
Section: Discussionmentioning
confidence: 99%